Kinerja Sekolah Dalam Upaya Meningkatkan Mutu Pendidikan Di SD Negeri Sampangan No.26 Tahun 2016 - Nur Afifah, Siti, Drs. Rubino Rubiyanto, M.Pd (2017)
This study aimed to describe: (1) planning the school's performance in improving the quality of school education; (2) the implementation of the school's performance in improving the quality of education; (3) obstacles in the implementation of performance in order to improve the quality of education. This study uses qualitative research with ethnographic research design. This study obtained data from the data sources that principals and teachers. The technique used for data collection is interview, observation and documentation. This study uses triangulation sources and triangulation methods, as well as use interactive analysis techniques. The results of this study concluded that: (1) in the preparation of the performance of the school in an effort to improve the quality of education must prepare: (a) input, (b) output, (c) outcomes, (d) benefits, (e) impact; (2) in the implementation of the performance of schools in an effort to improve the quality of education should do (a) accountability for performance; (b) the evaluation of performance; (c) financial accountability; (3) The obstacles to the implementation of the performance of the school in an effort to improve the quality of education that is for senior teachers is not all control of IT, and participation of parents of learners is still lacking, because when the school invites parents of learners for the procurement of communication about education, people older learners are not fully come (10-20% did not attend).